The impact of practicing sports and physical activities on life quality level among a sample of master’s students after the Corona pandemic - Makhlouf Djerioui; Abderrahim Laidi; Ahmed Lebchiri (Physical Education of Students)
Background and Study Aim. Research has shown that practicing sports and physical activities positively influences the quality of life level for master’s students. This research aims to identify the standard levels of life quality among master’s students practicing physical activities after the Corona pandemic.